Ultrathin flexible piezoelectric sensors for monitoring eye fatigue. (9th January 2018) - Lü, Chaofeng; Wu, Shuang; Lu, Bingwei; Zhang, Yangyang; Du, Yangkun; Feng, Xue
Abstract: Eye fatigue is a symptom induced by long-term work of both eyes and brains. Without proper treatment, eye fatigue may incur serious problems. Current studies on detecting eye fatigue mainly focus on computer vision detect technology which can be very unreliable due to occasional bad visual conditions. As a solution, we proposed a wearable conformal in vivo eye fatigue monitoring sensor that contains an array of piezoelectric nanoribbons integrated on an ultrathin flexible substrate. By detecting strains on the skin of eyelid, the sensors may collect information about eye blinking, and, therefore, reveal human's fatigue state. We first report the design and fabrication of the piezoelectric sensor and experimental characterization of voltage responses of the piezoelectric sensors. Under bending stress, the output voltage curves yield key information about the motion of human eyelid. We also develop a theoretical model to reveal the underlying mechanism of detecting eyelid motion. Both mechanical load test and in vivo test are conducted to convince the working performance of the sensors. With satisfied durability and high sensitivity, this sensor may efficiently detect abnormal eyelid motions, such as overlong closure, high blinking frequency, low closing speed and weak gazing strength, and may hopefully provide feedback for assessing eye fatigue in time so that unexpected situations can be prevented.